Characterization of crude oil viscosity change under laser irradiation. (1st December 2022) - Zhang, Shanzhe; Sun, Xiaorong; Zheng, Dongyu; Liu, Cuiling; Miao, Xinyang; Zhao, Kun
Abstract: Heavy crude oil is a type of crude oil that has high viscosity, which leads to poor fluidity. In this paper, a 532 nm laser was employed to reduce the oil viscosity at low current. The voltage, temperature and the viscosity will change under laser irradiation. Under laser irradiation, the photon energy was absorbed by liquid and converted into heat energy, leading to the temperature rise. Furthermore, the rise in temperature led to breaking of the hydrogen bonds, which resulted in the drop in the viscosity v . Due to the thermal effect induced by the laser, the variation of viscosity Δ v was closely related to the laser irradiation position. The results of the experiments suggest that laser technology could be applied to characterize the viscosity change in crude oil under laser irradiation.